APLIKASI PUPUK PELENGKAP CAIR ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (brassica juncea L.) - Abdi Firmansyah; Nurbaiti '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The study aims to determine the effectiveness of applications of supplemental liquid organic fertilizer and get the best concentration on the growth and yield of mustard (Brassica juncea L.) This research was conducted at the experimental station faculty of agriculture, University of Riau in january to februari 2014. Completely randomized design with 4 treatment and 5 replication use in this experiment. The treatment consisted application of supplemental liquid organic fertilizer with concentration is :P0 : without application of supplemental liquid organic fertilizer, P1 : supplemental liquid organic fertilizer concentration 1 cc/l of water, P2 : supplemental liquid organic fertilizer concentration 2 cc/l of water and P3 : supplemental liquid organic fertilizer concentration 3 cc/l of water. Data were analyzed using analysis of variance and mean separation with Duncan Multiple Range Test at the 5% level. The parameters measured were the plant height, leaf number, leaf area, plant fresh weight and weight of crop suitable for consumption. The results showed that application of supplemental liquid organic fertilizer significantly affected to parameters of plant height, leaf number, leaf area, plant fresh weight and weight of crop suitable for consumption. Application of supplemental liquid organic fertilizer at concentrations 3 cc /l of water is the best concentration for all parameters tested. Keyword : Mustard, liquid organic fertilizer,Growth, Yield